2021
DOI: 10.1093/gigascience/giaa159
|View full text |Cite
|
Sign up to set email alerts
|

Genome diversity in Ukraine

Abstract: Background The main goal of this collaborative effort is to provide genome-wide data for the previously underrepresented population in Eastern Europe, and to provide cross-validation of the data from genome sequences and genotypes of the same individuals acquired by different technologies. We collected 97 genome-grade DNA samples from consented individuals representing major regions of Ukraine that were consented for public data release. BGISEQ-500 sequence data and genotypes by an Illumina G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 57 publications
4
14
0
2
Order By: Relevance
“… 23 Ukrainian population show more prevalence to a different DNA repair gene; RAD51. 24 However, the South Korean population seem to have prevalence of deletion mutations in Sialic Acid Binding Ig Like Lectin 14 (SIGLEC14) 25 which is linked to inflammasome activation in macrophage. 26 Thus, the different mutations in the different populations may have role in shaping the transcriptomics profile in those populations.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Ukrainian population show more prevalence to a different DNA repair gene; RAD51. 24 However, the South Korean population seem to have prevalence of deletion mutations in Sialic Acid Binding Ig Like Lectin 14 (SIGLEC14) 25 which is linked to inflammasome activation in macrophage. 26 Thus, the different mutations in the different populations may have role in shaping the transcriptomics profile in those populations.…”
Section: Discussionmentioning
confidence: 99%
“…In the second stage of mapping worldwide genome diversity, national projects replaced the global surveys to serve as a major reference resource for human genetic variation and to provide locally based annotation of disease variants. National genome projects were supported by country governments [ 5 , 6 ], international collaborations [ 7 ], and/or groups of enthusiasts [ 8 ]. These efforts continued to contribute, without the unified systematic global strategy.…”
mentioning
confidence: 99%
“…Recently, analysis of the data from whole-genome studies, one in Ukraine [ 8 ] and one in Russia [ 24 ], clearly demonstrated that intrinsic genomic diversity from Eastern Europe had been poorly represented. The SNP allele frequency differences are large enough to provide previously unknown dimensions of population structure.…”
mentioning
confidence: 99%
See 2 more Smart Citations